Review E-Commerce dalam Perspektif Bisnis Syariah - Andi Iswandi (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2021)
Electronic sales or e-commerce is the distribution, purchase, sale, marketing of goods and services through electronic systems The development of digital technology is currently very fast, especially in the e-commerce sector. The intense competition has forced many parties to continue to innovate in order to survive in this era of disruption. This study aims to formulate e-commerce theory from a sharia perspective by discussing the themes (1) definition of e-commerce; (2) the concept and mechanism of e commerce; (3) the legitimacy of e-commerce in sharia business. The results of the discussion of this study state that e-commerce is a trading transaction system that uses electronic instruments for online shopping businesses. Transactions carried out in e-commerce via the internet are basically not different from as-salam transactions, except for commodities that are used as the object of the transaction. e-commerce transactions via the internet should be careful in making transactions, such as by checking the security system owned by merchants, having insight and knowledge about the commodities that are used as the object of transactions so as not to buy commodities that are not in accordance with existing norms, and also clearly check the date of delivery and place of delivery of the commodity so that disputes can be avoided. Finally, it is hoped that this will provide new opportunities in modern Islamic business activities.